Lactate/Albumin Ratio as a Prognostic Factor for Short-time Mortality in Critically Ill Patients with Coronavirus Disease-2019 - Abdullah Gök; Umut Sabri Kasapoğlu; Leman Acun Delen; Ferda Özmen; Süsen Banazılı (Galenos Yayinevi, 2021)
Objective:The prognostic role of the initial lactate/albumin ratio (LAR) in critically ill patients with coronavirus disease-2019 (COVID-19) remains unknown. This study aimed to evaluate the prognostic value of the initial LAR in predicting 30-day mortality in critically ill patients with COVID-19 and compare the initial level of serum lactate and albumin for mortality prediction.Materials and Methods:A single-center and observational clinical study between April 2020 and December 2020 were retrospectively performed. Clinical and laboratory variables of patients evaluated in this study were collected within the first 24 hours following the intensive care unit (ICU) admission.Results:A total of 282 critically ill patients with COVID-19 were included in the study. The mean age of the patients was 66.34±12.08 years, wherein 179 (63.5%) were male. Patients who died within 30 days had higher lactate (p<0.001), lower serum albumin (p<0.001), and higher LAR levels (p<0.001). ROC analysis revealed that LAR (AUC: 0.824) was superior to the serum albumin (AUC: 0.644) and lactate levels (AUC: 0.795) for mortality prediction. Overall ICU mortality rates (75.6% vs. 13.1%, p<0.001) were significantly higher in patients with LAR of >0.60.Conclusion:LAR is a useful prognostic factor for risk stratification of critically ill patients with COVID-19.